2019
DOI: 10.3390/molecules24081459
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cannabidiol in the Treatment of Epilepsy: Efficacy and Security in Clinical Trials

Abstract: Cannabidiol (CBD) is one of the cannabinoids with non-psychotropic action, extracted from Cannabis sativa. CBD is a terpenophenol and it has received a great scientific interest thanks to its medical applications. This compound showed efficacy as anti-seizure, antipsychotic, neuroprotective, antidepressant and anxiolytic. The neuroprotective activity appears linked to its excellent anti-inflammatory and antioxidant properties. The purpose of this paper is to evaluate the use of CBD, in addition to common anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
124
1
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(131 citation statements)
references
References 88 publications
0
124
1
6
Order By: Relevance
“…CBD functions as a negative allosteric modulator of CB 1 receptor (51). Therefore, it has therapeutic potential in the treatment of the central nervous system diseases (neurodegenerative diseases, epilepsy, anxiety, and depression) without concurrent psychotic side effects (2,52,53). Furthermore, it was indicated that CBD is able to block CB 1 receptor, thereby producing anti-obesity effects.…”
Section: Cannabidiol (Cbd)mentioning
confidence: 99%
See 1 more Smart Citation
“…CBD functions as a negative allosteric modulator of CB 1 receptor (51). Therefore, it has therapeutic potential in the treatment of the central nervous system diseases (neurodegenerative diseases, epilepsy, anxiety, and depression) without concurrent psychotic side effects (2,52,53). Furthermore, it was indicated that CBD is able to block CB 1 receptor, thereby producing anti-obesity effects.…”
Section: Cannabidiol (Cbd)mentioning
confidence: 99%
“…Currently, the first cannabis based medicine containing CBD/ 9 -THC combination for the multiple sclerosis related spasticity treatment (Sativex/Nabiximols; GW Pharmaceuticals) has been approved in numerous countries, including Australia, Canada, New Zealand and in most European Union countries (72). Furthermore, a drug composed solely of CBD (Epidiolex; GW Pharmaceuticals) has been approved in June 2018 in the United States for the treatment of Dravet and Lennox-Gastaut syndromes in children (52,73,74).…”
Section: Cannabidiol (Cbd)mentioning
confidence: 99%
“…The other indication awarded to GW was specific to DS, which a similar series of clinical trials were performed following preclinical research suggesting potential seizure reduction through its agonistic action on the CB1 and CB2 receptors (Anwar et al, 2019;Silvestro et al, 2019). The same titration method, dosage, and time of use was used to evaluate the safety and efficacy on patients suffering from DS; however, this study contained a smaller participant pool of 61 patients receiving the drug and 59 receiving the placebo.…”
Section: Epileptic Seizuresmentioning
confidence: 99%
“…Regarding oxidative stress, some of the current treatments could already be addressing this problem. In addition to DS, cannabidiol (CBD) is being used or in clinical trials for several types of epilepsy [194], and it has a neuroprotective effect by inhibiting nitric oxide production, one of the main neurotoxic effectors [195]. The ketogenic diet, high in fats and low in carbohydrates and proteins, is also widely used to treat refractory epilepsies [196].…”
Section: Oxidative Stress and Neuroinflammation As Therapeutic Targetmentioning
confidence: 99%